Підвищення надійності локальної мережі засобами агрегації портів на комутаторі - Ситніков, Р. С.; Крепко, А. В. (ХНУРЕ, 2024)
This paper analyzes the impact of different schemes for implementing port aggregation between switches on the reliability of a local information and communication network. Network topologies incorporating "bridges" were modeled using MATLAB. Analysis of the results provided a basis for recommendations on the optimal number of ports to include in aggregation, depending on the required reliability level of the local network's communication links.
Keywords: локальна мережа; комутатор; агрегація портів